1967
DOI: 10.1080/00362176785190201
|View full text |Cite
|
Sign up to set email alerts
|

Speciation and densities of yeasts in human urine specimens

Abstract: Urine specimens from 1013 patients were selectively and quantitatively cultured for yeasts. The presence of yeasts was correlated with the age, sex, and physical condition of the individual. Yeasts occurred at an incidence of 17-6% with approximately 6% of the patients demonstrating urine populations of at least 105 yeast cells/ml. Candida albicans, Torulopsis glabrata, and C. tropicalis were the most common species isolated. These taxa occurred in high densities most frequently among diabetics and terminal pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

1971
1971
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(10 citation statements)
references
References 15 publications
0
9
0
1
Order By: Relevance
“…In this department T. glabrata was found in 82 of 234 midstream and catheter urines yielding 104 or more colonies per ml of yeasts (Speller and Davies, 1973) and it is likely that infection by this organism is commoner than has been thought. Ahearn, Jannach, and Roth (1966) isolated T. glabrata from 45 of 1013 urine specimens and noted that nine of the patients had diabetes mellitus. The association with diabetes has been noted by others (Guze and Haley, 1958;Edebo and Spetz, 1965;Marks et al, 1970) and Hasenclever and Mitchell (1962) showed increased multiplication of T. glabrata in the kidneys of mice when they were made diabetic with alloxan.…”
Section: Commentmentioning
confidence: 99%
“…In this department T. glabrata was found in 82 of 234 midstream and catheter urines yielding 104 or more colonies per ml of yeasts (Speller and Davies, 1973) and it is likely that infection by this organism is commoner than has been thought. Ahearn, Jannach, and Roth (1966) isolated T. glabrata from 45 of 1013 urine specimens and noted that nine of the patients had diabetes mellitus. The association with diabetes has been noted by others (Guze and Haley, 1958;Edebo and Spetz, 1965;Marks et al, 1970) and Hasenclever and Mitchell (1962) showed increased multiplication of T. glabrata in the kidneys of mice when they were made diabetic with alloxan.…”
Section: Commentmentioning
confidence: 99%
“…Germ-tube production by Candida albicans occurs in mammalian serum and serum substitutes (7,11,13), plasma (3), egg white (4), human saliva (2), and a complex tissue culture medium (1). This morphological characteristic of C. albicans has also been used as an aid in the laboratory identification of C. albicans.…”
Section: Introductionmentioning
confidence: 99%
“…The yeasts isolated in this investigation were those commonly encountered in such specimens (Ahearn et al, 1966;Speller and Davies, 1973). The funguria series and the control bacteriuria series differed in several important clinical features.…”
Section: Discussionmentioning
confidence: 80%
“…As with bacteriuria, quantitative criteria can be applied (Ahearn et al, 1966), and in fresh specimens a count of 105 or more colonyforming units per millilitre almost certainly implies that the yeast is not a contaminant but is genuinely colonizing the bladder urine. Most of the patients with significant funguria, however, appear to suffer no ill effects from this, often persistent, colonization (Schonebeck, 1972) and it is only the occasional patient in whom dramatic complications develop-blood stream or tissue invasion, urinary obstruction, etc.…”
mentioning
confidence: 99%